2019
DOI: 10.1017/s1460396918000742
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an in-house developed monitor unit double-check program for 3D conformal radiation therapy and treatment planning system verification

Abstract: AimThe treatment planning system (TPS) plays a key role in radiotherapy treatments; it is responsible for the accurate determination of the monitor unit (MU) needed to be delivered to treat a patient with cancer. The main goal of radiotherapy is to sterilise the tumour; however, any imprecise dose delivered could lead to deadly consequences. The TPS has a quality assurance tool, an independent program to double check the MU, evaluate patient plan correctness and search for any potential error.Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…confirmed that the differences in MU between manual and TPS calculations for breast radiotherapy increase when these calculations require OAR(r) corrections, and compared 6 MV and Cobalt beams (the OAR correction is neglected for Co‐60) under similar conditions while neglecting influencing factors such as tissue heterogeneities in both calculations. Also, computerized investigations proved that these differences are small at the IC and large away from it under the same conditions 3,24,37 . In addition, Ian et al 25,26 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…confirmed that the differences in MU between manual and TPS calculations for breast radiotherapy increase when these calculations require OAR(r) corrections, and compared 6 MV and Cobalt beams (the OAR correction is neglected for Co‐60) under similar conditions while neglecting influencing factors such as tissue heterogeneities in both calculations. Also, computerized investigations proved that these differences are small at the IC and large away from it under the same conditions 3,24,37 . In addition, Ian et al 25,26 .…”
Section: Discussionmentioning
confidence: 91%
“…The S cp , S cp , D f %, and 𝚫 S cp were calculated from Equations (3), ( 5), (6), and (7) Also, computerized investigations proved that these differences are small at the IC and large away from it under the same conditions. 3,24,37 In addition, Ian et al 25,26 proved, after correcting the missing tissue in breast, that these differences increase with the decreasing energy of the photon beam. Part of the remaining unresolved difference in MUs can be explained by the fact that the equivalent field in the TPS is defined as the symmetric field in which the PDD of its central axis has the same properties as the PDD in the effective axis of the asymmetric field,and this also applies to the S cp .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations